2018
DOI: 10.2337/dci17-0029
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health-Related Quality of Life in Patients With Diabetic Foot Disease: Why Is It Important and How Can We Improve? The 2017 Roger E. Pecoraro Award Lecture

Abstract: Patient-reported outcomes (PROs) have become an important subject in the area of diabetes-related foot complications. Self-reported health-related quality of life (HRQOL) surveys can provide a generic measure of overall health (global) and can be disease specific (i.e., diabetes) or even region specific (i.e., lower-extremity function). Analysis of PRO measures utilizing validated instruments allows health care providers to determine whether medical and surgical treatments are providing patients with the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 55 publications
3
74
0
2
Order By: Relevance
“…Due to its subjectivity, HRQoL is assessed as patient-reported outcome (PRO). It is considered an important outcome measure of medical treatment in addition to the clinical outcome measures [9]. Nowadays, HRQoL questionnaires are widely used and play a major role in healthcare decisions and treatment evaluation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its subjectivity, HRQoL is assessed as patient-reported outcome (PRO). It is considered an important outcome measure of medical treatment in addition to the clinical outcome measures [9]. Nowadays, HRQoL questionnaires are widely used and play a major role in healthcare decisions and treatment evaluation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Of all the variables included in the model, we observed that “low educational level” increases the risk of losing protective sensitivity (OR: 31.4, 95% CI: 2.5‐383.3, P = .007); however, the confidence interval is quite high, so the risk—although present—may be overestimated by the sample size. Those with a lower level of education typically have poorer health habits, causing increased obesity, physical inactivity, and susceptibility to psychosocial risks, which increases the risk of suffering from neuropathy . Therefore, it is important to establish preventative programs aimed at less educated populations to reduce the prevalence of PN.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18] Assessing the health-related quality of life (HRQOL) provides an opportunity to address specific physical or mental health concerns of patients. 16 Patients with diabetic foot ulcers often report low HRQOL.…”
Section: Discussionmentioning
confidence: 99%